2023
DOI: 10.3390/make5010013
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning and Prediction of Infectious Diseases: A Systematic Review

Abstract: The aim of the study is to show whether it is possible to predict infectious disease outbreaks early, by using machine learning. This study was carried out following the guidelines of the Cochrane Collaboration and the meta-analysis of observational studies in epidemiology and the preferred reporting items for systematic reviews and meta-analyses. The suitable bibliography on PubMed/Medline and Scopus was searched by combining text, words, and titles on medical topics. At the end of the search, this systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Santangelo and colleagues concluded that it is feasible to anticipate the emergence and progress of some infectious illnesses in this respect after conducting a comprehensive study with the goal of demonstrating whether it is possible to predict the spread of infectious diseases early using ML. Additionally, they said that correct and respectable outcomes may be obtained by integrating a variety of methods and ML algorithms 43 . Therefore, it would seem that, with additional development, the ML algorithm‐based prediction model might complement the present approaches for identifying high‐risk patients and grow to be a valuable tool for clinical staff in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Santangelo and colleagues concluded that it is feasible to anticipate the emergence and progress of some infectious illnesses in this respect after conducting a comprehensive study with the goal of demonstrating whether it is possible to predict the spread of infectious diseases early using ML. Additionally, they said that correct and respectable outcomes may be obtained by integrating a variety of methods and ML algorithms 43 . Therefore, it would seem that, with additional development, the ML algorithm‐based prediction model might complement the present approaches for identifying high‐risk patients and grow to be a valuable tool for clinical staff in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous research have employed ML approaches to forecast infectious outbreaks in recent years, with encouraging outcomes. Previous research findings have demonstrated that ML algorithms may predict infectious illness onset and spread with an accuracy that is on par with or better than that of classic statistical methods 43 . A thorough summary of meningitis diagnosis methods must be given due to the multitude of new procedures that are being developed.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning algorithms can analyze large, complex data sets and identify patterns and trends that are difficult to be detected by humans. For this reason, an increasing number of studies in recent years have applied them to predict infectious disease outbreaks 21 . Random Forest 22 is one of the most commonly used and most powerful machine learning techniques or this purpose 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Traditional approaches to disease surveillance and control often fall short due to their inherent limitations in handling the complexities of large-scale data, diverse variables, and non-linear relationships 4 . Herein lies the potential of machine learning to revolutionize disease prediction and management 5 .…”
Section: Introductionmentioning
confidence: 99%